The potential roles of androgen and estrogen receptors during reproductive cycle in Pampus argenteus - Zhongsu Wan; Ming Ding; Xinru Zhang; Chang Li; Jiajie Zou; Danli Wang; Xubo Wang; Chunyang Guo (PLoS ONE, 2026)
Steroid hormones are indispensable for regulating the typical reproductive processes during the development of gonads. This study aimed to clarify the expression patterns of androgen receptors (Ars) and estrogen receptors (Ers) in Pampus argenteus to better understand gonadal development and improve artificial breeding. In this study, the androgen receptors ( arα and arβ ) and estrogen receptors ( esr1, esr2a , and esr2β ) of P. argenteus were cloned and the expression profiles were detected by qPCR. The results showed that the highest expression of arα was found in hypothalamus, while arβ was mainly found in midbrain of male fish. The esr1 , esr2β and esr2α showed the highest expression level in pituitary, ovary, and liver of female fish, respectively. During the gonadal development, arα and arβ reached their highest expression in stage IV, while esr1 , esr2a , and esr2β showed the strongest expression in stage V in the ovary. In the testis, arα and esr2β showed the highest expression in stage I, arβ peaked in stage II, and esr1 and esr2a reached their highest levels in stage IV. In the pituitary, arα peaked during stage IV of ovarian development, while esr1 , esr2a , and esr2β all exhibited sex- and stage-specific expression partterns. Hormone treatment results showed that in ovarian tissue, E2 significantly upregulated arα , arβ , and all ers . In testicular tissue, MT markedly promoted the expression of arα , arβ , and all ers , and the combined E2 + MT treatment also synergistically enhanced arβ expression. Taken together, Ars and Ers exhibit distinct tissue- and stage-specific roles in gonadal development, with Ars primarily involved in early gametogenesis and Ers in later maturation. Their complementary, hormone-responsive functions provide a molecular basis for asynchronous gonadal development and offer guidance for improving artificial breeding of P. argenteus .